ANALISIS PERAN KOMITE DALAM PENGADAAN SARANA DAN PRASARANA - Rina Amahorosea; Sihminto Sihminto (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2022)
The school committee is an independent body that functions as a forum for community participation in the context of improving the quality, equity and efficiency of the delivery of education in educational institutions, both in preschool education, school education, and out of school education. . The aim of this research is to explain; (1) the business of procuring facilities and infrastructure, (2) knowing the role of the school committee in procuring facilities and infrastructure. The focus of this research is; (1) procurement of facilities and infrastructure, (2) the role of the school committee in procuring facilities and infrastructure. Researchers used descriptive qualitative research methods, data collection techniques used in this study were in-depth interviews, participant observation and documentation studies. Data validation technique uses triangulation. The results and conclusions in this study are; (1) the role and function of the committee as an advisory agency, support (supporting agency), controller (controlling agency) and mediator between the government (executive) and the community in the education unit (2) the role of the school committee in procuring school facilities and infrastructure is very necessary because with Adequate facilities, learning activities can run optimally in accordance with the expected educational goals